Comparative quantitative assessment of the placement and intensity of laser spots for treating diabetic macular edema - E.A. Zamytskiy; A.V. Zolotarev; E.V. Karlova; N.Yu. Il’yasova; A.S. Shirokanev (РМЖ "Клиническая офтальмология")
E.A. Zamytskiy1, A.V. Zolotarev1, E.V. Karlova1, N.Yu. Il’yasova2, A.S. Shirokanev2 1Samara State Medical University, Samara, Russian Federation 2Image Processing Systems Institute — Branch of the Federal Scientific Research Centre “Crystallography and Photonics” of RAS, Samara, Russian Federation Aim: to compare the uniformity and adequacy of the placement of laser spots after mono-impulse and pattern photocoagulation for diabetic macular edema (DME). Patients and Methods: fundus photographs of 83 patients (121 eyes) taken right after retinal photocoagulation for DME were analyzed. Group 1 included images of 63 eyes after pattern photocoagulation and group 2 included images of 58 eyes after mono-impulse photocoagulation. Laser burns of varying intensity based on LʹEsperance scale (including grade 0 burns that were not seen on fundus photos) were calculated. Grade 2 burns were considered optimal. The number of non-optimal laser burns placed on retinal hemorrhages, blood vessels, hard exudates or healthy retina was calculated. The uniformity of the position of laser spots was assessed by calculating the standard deviation from the average distance between laser spots. Results: the percentage of laser spots of optimal intensity was 31.85% in group 1 and 25.15% in group 2. The percentage of non-optimally placed laser spots was 24.34% in group 1 and 7.99% in group 2. The uniformity of the placement was good in both groups (8.16 pixels and 8.44 pixels, respectively), no significant difference was reported (p=0.0591). Conclusion: pattern photocoagulation is preferable for DME compared to mono-impulse photocoagulation to provide adequate intensity of laser burns. Meanwhile, mono-impulse regimen provides more precise placement of laser spots. However, both conventional techniques are not effective enough due many intrinsic drawback, i.e., many laser spots are non-optimal in terms of intensity or placement. In routine practice, these drawbacks are outweighed by the skills and experience of laser surgeon. Planned precise placement of laser spots and the introduction of techniques of more precise preventive adjustment of energy level for each laser spot will contribute to the maximum effect of photocoagulation for DME. Further studies on personalized precise laser photocoagulation will improve the quality and efficacy of the treatment of macular edema. Keywords: diabetic retinopathy, diabetic macular edema, mono-impulse photocoagulation, pattern photocoagulation, navigated photocoagulation. For citation: Zamytskiy E.A., Zolotarev A.V., Karlova E.V. et al. Comparative quantitative assessment of the placement and intensity of laser spots for treating diabetic macular edema. Russian Journal of Clinical Ophthalmology. 2021;21(2):58–62. DOI: 10.32364/2311-7729-2021-21-2-58-62.